A conformational switch in clathrin light chain regulates lattice structure and endocytosis at the plasma membrane of mammalian cells - Kazuki Obashi; Kem A. Sochacki; Marie-Paule Strub; Justin W. Taraska (Nature Communications, 2023)
Conformational changes within proteins are thought to regulate clathrin-mediated endocytosis. Here, authors develop a correlative FRET and EM imaging method and uncover a structural switch in clathrin light chain that controls endocytosis in cells.